A novel role of MMP-13 for murine DC function: its inhibition dampens T-cell activation. (26th February 2016) - Bartmann, Juliane; Frankenberger, Marion; Neurohr, Claus; Eickelberg, Oliver; Noessner, Elfriede; von Wulffen, Werner
Abstract : MMP-13 is crucial for many diverse functions in dendritic cells Abstract : Dendritic cells (DCs) have been shown to express matrix metalloproteinase 13 (MMP-13), but little is known about its specific function in DCs and its role in inflammatory conditions. In the present study, we describe a novel role of MMP-13 in regulating the immunostimulatory function of murine DCs through moderating MHC-I surface presentation, endocytosis and cytokine/chemokine secretion. MMP-13 expression was confirmed in bone marrow-derived DCs at both the mRNA and the protein level and, furthermore, at the activity level. Remarkably, LPS treatment strongly enhanced MMP-13 mRNA expression as well as MMP-13 activity, indicating an important role of MMP-13 in inflammatory processes. Functionally, MMP-13 inhibition did not influence the DC migratory capacity, while endocytosis of ovalbumin was significantly decreased. Inhibition of MMP-13 lowered the capability of murine DCs to activate CD8 + T cells, apparently through reducing MHC-I surface presentation. Decreased surface expression of CD11c on DCs, as well as changes in the DC cytokine/chemokine profile after MMP-13 inhibition, emphasizes the influence of MMP-13 on DC function. Moreover, T-cell-targeting cytokines such as IL-12, IL-23 and IL-6 were significantly reduced. Collectively, our data reveal a novel involvement of MMP-13 in regulating DC immunobiology through moderating MHC-I surface presentation, endocytosis and cytokine/chemokine secretion. Furthermore, the reduced MHC-I surface presentation by DCs resulted in a poor CD8 + T-cell response in vitro . This novel finding indicates that MMP-13 might be a promising target for therapeutic intervention in inflammatory diseases.